Development Planning During The Covid-19 Pandemic And The New Normal In Indonesia - Jam'an Jam'an (Journal of Governance, 2022)
To overcome various problems that arise during the pandemic, the government has modified the policies of countries abroad that use regional quarantine policies or lockdowns as large-scale social restrictions (PSBB). This policy is adapted to different levels of severity in each city, district, and province. The Indonesian economy itself experienced a slight slowdown during this pandemic period. This slowdown could cause Indonesia’s economic growth to experience a minus level in the following years. Therefore, the government needs to make new policies for the Indonesian economy during the pandemic period and the new normal era. This study aims to see how the government’s policies will overcome the problems of the COVID-19 pandemic and the new normal era for development planning in Indonesia. This research will use a qualitative approach with data obtained from various previous studies and studies related to this research. The study results found that there was a need for a scenario to be created by the government to deal with this problem. Then the economy can be reactivated through cultural changes that are pretty significant in people’s daily behaviors.